PENDEKATAN INTEGRATIF DALAM KEMAMPUAN MEMBACA PEMAHAMAN PADA PELAJARAN BAHASA INDONESIA TEMA 7 INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SEKOLAH DASAR - Friani Pertiwi; Nelis Supriati; Dedi Suherman (IKIP Siliwangi, 2022)
AbstractBasically, the factors that influence reading comprehension skills are the characteristics of the reading material and the characteristics of the readers. Comprehension is at the heart of the act of reading. Ironically, reading with understanding has been under-paid and under-understood by researchers even today. The purpose of this study was to determine the achievement and implementation of learning, teacher responses and students' reading comprehension skills, and the difficulties experienced by students in their reading comprehension skills. The method used in this research is descriptive qualitative. The number of samples in this study were 34 grade IV students of SDN 234 Saluyu, Bandung City for the 2019/2020 academic year. The results showed that from 34 respondents who were studied gave the reading comprehension of students through an integrative approach, the class average score was 80.88 (eighty point eighty eight). The average value of the students' reading comprehension ability was in the good category, then the highest score obtained was 100.00 (one hundred point zero) and the lowest score obtained was 60.00 (sixty point zero). From this data there are still students who score below the KKM. Teacher responses and students' reading comprehension skills when using the method of the integrative approach are positive and very good. The difficulties faced during the study included students who were unfamiliar with the method, lack of learning time, lack of teacher supervision, students were not used to working on Student Worksheets, and there were students who were dissatisfied with the division of the group.Keywords: Reading comprehension, integrative approach Abstrak Pada dasarnya, faktor yang mempengaruhi kemampuan membaca pemahaman yaitu karakteristik materi bacaan dan karakteristik pembaca. Pemahaman adalah jantung dari tindakan membaca. Ironisnya, membaca dengan pemahaman kurang diperhatikan dan kurang dipahami oleh para peneliti bahkan hingga kini. Tujuan penelitian ini adalah untuk mengetahui pencapaian dan implementasi pembelajaran, respon guru dan kemampuan membaca pemahaman siswa, seta kesulitan yang dialami siswa dalam kemampuan membaca pemahaman. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Jumlah sampel dalam penelitian ini adalah 34 siswa kelas IV SDN 234 Saluyu Kota Bandung Tahun Pelajaran 2019/2020. Hasil penelitian menunjukkan dari 34 responden yang diteliti memberikan hasil membaca pemahaman siswa melalui pendekatan integratif diperoleh nilai rata-rata kelas sebesar 80,88 (delapan puluh koma delapan puluh delapan). Nilai rata-rata kemampuan membaca pemahaman siswa tersebut tergolong dalam kategori baik, selanjutnya nilai tertinggi yang diperoleh sebesar 100,00 (seratus koma nol) dan Nilai terendah yang diperoleh adalah 60,00 (enam puluh koma nol). Dari data tersebut masih ada siswa yang mendapat nilai di bawah KKM. Respon guru dan kemampuan membaca pemahaman siswa ketika menggunakan motode pendekatan integratif positif dan sangat baik. Kesulitan-kesulitan yang dihadapi selama penelitian diantaranya siswa belum mengenal metode, kurangnya waktu pembelajaran, kurangnya pengawasan guru, siswa tidak terbiasa mengerjakan Lembar Kerja Siswa, dan terdapat siswa yang tidak puas dengan pembagian kelompok.Kata Kunci: Membaca pemahaman, pendekatan integratif.